MOLECULAR AND PHYSIOLOGICAL CHARACTERIZATION OF Fusarium oxysporum ciceri ISOLATES FROM DIFFERENT CHICKPEA AREAS IN IKR, IRAQ - Emad M. Al-Maaroof; Kazhal H. Rahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Thirty-seven different F. oxysporum ciceri isolates were isolated from 55 chickpea fields at Sulaimani and Halabja governorates during 2021. Fourteen Foc isolates were pathogenic and displayed various morphological traits. The ideal temperature for Foc ranged 25-30°C. PDA was the best media for the fungal growth. The isolates showed a variety of growth patterns, including appressed, flat/velvet, fluffy to partial fluffy, and cottony. However, Foc-28 displays nerve type mycelium growth on PDA at 25ºC. Microconidia (6.1-8.7x2.9-4.98µm), macroconidia (10.0-20.1x2.7-5.2µm), chlamydospores (7.2-15.0x6.8-10.7µm), and colony diameter on PDA were all significantly differed among the isolates. Significant differences in virulence of 14 Foc isolates were detected on 10 chickpea wilt differentials. The isolates were classified in to two groups and ten physiological races accordingly. Each isolate’s genomic DNA was amplified by the ITS primers to a maximum size of 400bp, producing a single band for each accession. The basic local alignment search tool (BLAST) analysis supported the morphological identification, whereby the closest match 99-100% in the NCBI GenBank database. The accession numbers for the sequences were registered at the NCBI gen bank under different codes. The phylogenetic tree proposed two major clades with stains distributed across the dendrogram irrespective of their geographic status.